2020
DOI: 10.1007/s00784-020-03549-1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical pilot study on the effects of a hydrogen peroxide mouthrinse on the intraoral viral load of SARS-CoV-2

Abstract: Objectives SARS-CoV-2 is mainly transmitted by inhalation of droplets and aerosols. This puts healthcare professionals from specialties with close patient contact at high risk of nosocomial infections with SARS-CoV-2. In this context, preprocedural mouthrinses with hydrogen peroxide have been recommended before conducting intraoral procedures. Therefore, the aim of this study was to investigate the effects of a 1% hydrogen peroxide mouthrinse on reducing the intraoral SARS-CoV-2 load. Methods Twelve out of 9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(155 citation statements)
references
References 34 publications
1
138
0
7
Order By: Relevance
“…Hydrogen peroxide mouthwash in one study reduced viral titers in three separate strains of SARS-CoV-2 but the reduction was not significant [ 18 ]. In one clinical pilot study of ten SARS-CoV-2 positive patients hydrogen peroxide 1% was not shown to reduce intraoral viral load [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide mouthwash in one study reduced viral titers in three separate strains of SARS-CoV-2 but the reduction was not significant [ 18 ]. In one clinical pilot study of ten SARS-CoV-2 positive patients hydrogen peroxide 1% was not shown to reduce intraoral viral load [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the in vitro data available for hydrogen peroxide suggests, it is less effective than PVP-I and Listerine in reducing the viral load of SARS-CoV-2 in the oral cavity [ 18 ]. One small study of hydrogen peroxide in ten patients reported no significant reduction of intraoral viral load in SARS-CoV-2 positive patients [ 48 ]. Hydrogen peroxide has been considered safe to use as a tooth-whitening treatment, but may cause tooth sensitivity and gingival irritation which is concentration dependent [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective, in vivo, clinical pilot study, Gottsauner et al (2020) used RT-PCR to analyze the effect of gargling in the mouth and throat with 20 mL of 1% hydrogen peroxide for 30 s. No control group (e.g., a placebo mouth rinse without hydrogen peroxide) was included. Among the 10 COVID-19 patients included, there was no significant decrease in SARS-CoV-2 viral load.…”
Section: Mouth Rinse Reagents With In Vitro or In Vivo Anti–sars-cov-mentioning
confidence: 99%
“…Aber auch epidemiologische Themen, wie das Auftreten von COVID-Fällen unter HNO-Ärzten [ 15 ], infektiologische Grundlagenarbeiten, wie z. B. die Entstehung und Verteilung von Aerosolpartikeln [ 16 , 17 ], oder auch Interventionsstudien zum Effekt von Mundspülungen auf die Viruslast [ 18 ] wurden bearbeitet. Ebenfalls wurden Publikationen zur Einführung digitaler Medien für die Patientenversorgung [ 19 ] und die studentische Lehre [ 20 , 21 ] erstellt.…”
Section: Diskussionunclassified